ECONOMIC FOUNDATIONS OF IT-ENTERPRISES IN THE CONTEXT OF A CREATIVE APPROACH - PAVLOV, Kostiantyn; PAVLOVA, Olena; ZAKRYZHEVSKYI, Maksym; OPASHNYUK, Yuriy (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article discusses the concept of "creative economy" and analyzes the creative approach’s role in modern IT companies’ economic activity. Also, the importance of innovative thinking in the strategic planning and development of IT enterprises is investigated. Innovative solutions and their creative application are the most valuable resources, and creativity is becoming the primary source of economic value in the modern world. The critical components of the creative approach and their impact on the efficiency and competitiveness of IT companies in modern conditions are highlighted. The author analyzes how the creative economy contributes to developed countries’ rapid growth and economic development and the prospects for its integration. The modern economy is increasingly based on using creative resources and intellectual capital to transform into innovative ideas and products. The success of IT companies in the market depends on an effective combination of creativity, technological innovation, and entrepreneurial initiative. For Ukraine, the concept of creativity and innovative entrepreneurship, especially in the IT sector, is relatively new. However, it has existed in highly developed countries for over two decades. Ukraine’s IT sector shows dynamic growth, playing a vital role in the national economy. Increasing the professionalism of IT specialists and attracting international investment is helping to consolidate Ukraine as an essential player in the global IT arena. Successful management of enterprises in this industry is critical to ensuring their competitiveness and stability. Using a creative approach and a well-defined Strategy, Ukrainian IT companies can adapt to changes in the external and internal environment, introduce innovations, and ensure economic development. The development of IT companies with a creative approach is critical for the economy, as it improves job creation and income for highly skilled workers, raises living standards through the development of digital infrastructure, and introduces innovations in various sectors of the economy. The efficient operation of IT companies also attracts investment, stimulates entrepreneurship development in related sectors of the economy, and increases tax revenues.